2020
DOI: 10.3390/microorganisms8121993
|View full text |Cite
|
Sign up to set email alerts
|

HCoV-NL63 and SARS-CoV-2 Share Recognized Epitopes by the Humoral Response in Sera of People Collected Pre- and during CoV-2 Pandemic

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause serious illness in older adults and people with chronic underlying medical conditions; however, children and young people are often asymptomatic or with mild symptoms. We evaluated the presence of specific antibodies (Abs) response against Human coronavirus NL63 (HCoV-NL63) S protein epitopes (NL63-RBM1, NL63-RBM2_1, NL63-RBM2_2, NL63-RBM3, NL63-SPIKE541–554, and NL63-DISC-like) and SARS-CoV-2 epitopes (COV2-SPIKE421–434 and COV2-SPIKE742–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
4
30
0
Order By: Relevance
“…This status had no influence on the antibody response against SARS-CoV-2 [42]. Similarly, the findings of Simula et al (2020) showed that antibodies against NL63 have the potential to cross-react against SARS-CoV-2 spike protein [43]. The preexisting humoral responses against SARS-CoV-2 were also reported to be against N and spike proteins [44,45].…”
Section: Pre-existing Antibodies In the Individuals Against Sars-cov-2 In The Absence Of Virus Infectionmentioning
confidence: 81%
“…This status had no influence on the antibody response against SARS-CoV-2 [42]. Similarly, the findings of Simula et al (2020) showed that antibodies against NL63 have the potential to cross-react against SARS-CoV-2 spike protein [43]. The preexisting humoral responses against SARS-CoV-2 were also reported to be against N and spike proteins [44,45].…”
Section: Pre-existing Antibodies In the Individuals Against Sars-cov-2 In The Absence Of Virus Infectionmentioning
confidence: 81%
“…In the context of the COVID-19 pandemic, there are a growing number of studies on the seroprevalence of antibodies to HCoV-NL63 [8,17,18]. Most have utilised serological assays that test for recognition of viral peptides that may not reflect functional antibody (neutralising) activity, making comparisons to our study difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity with seasonal coronaviruses has to be considered. Even if recently, pre-existing HCoV-NL63 antibody response crossreacting with some SARS-CoV-2 antigens was detected in both pre-and mid-pandemic infected individuals [28], though no cross-reactivity of serology methods with the seasonal coronavirus was reported [29] and no neutralizing activity of SARS-CoV-2 in pre-pandemic sera was observed [30]. All IgT-positive serum samples were positive for antibodies against the RBD of S protein (Biosynex COVID19 BSS).…”
Section: Discussionmentioning
confidence: 99%